THE EFFECT OF ORGANISATIONAL ACTIVITY AND SELF-EFFICACY ON STUDENT ACHIEVEMENT INDEX - Asri Nur Muin; Sukardi Sukardi; Muhammad Nurhusain (SEAN Institute, 2022)
This study aims to determine the effect of organisational activity and self-efficacy on student achievement indexes for students who are actively organised in the internal campus organisations of STIE YPUP Makassar and STKIP YPUP Makassar for the 2021–2022 period. Studying this is studying